MUC-1 expression in pleomorphic adenomas using two human milk fat globule protein membrane antibodies (HMFG-1 and HMFG-2) - Santa PONCE-BRAVO; Constantino LEDESMA-MONTES; Maricela GARCÉS-ORTÍZ (University of São Paulo, 2015)
Pleomorphic adenoma (PA) is the most common salivary gland tumor and its microscopic features and histogenesis are a matter of debate. Human milk fat globule protein membrane (HMFG) monoclonal antibodies (MoAbs) comprise a set of antibodies against the mucin 1 (MUC-1) protein detected in several salivary gland tumors. Objective The aim of this study was to assess the immunoexpression of the PA neoplastic cells to MUC-1 protein using HMFG-1 and HMFG-2 MoAbs, contrasting these results with those from normal salivary gland tissue. Material and Methods Immunohistochemical detection of MUC-1 protein using HMFG-1 and HMFG-2 MoAbs was made in 5 mm thick, paraffin embedded slides, and the avidin-biotin method was used. Results Positivity to HMFG-1 and HMFG-2 MoAbs was found in ductal, squamous metaplastic and neoplastic myoepithelial cells, keratin pearls and intraductal mucous material. Two kinds of myoepithelial cells were identified: classic myoepithelial cells around ducts were negative to both MoAbs, and modified myoepithelial cells were positive to both MoAbs. This last cellular group of the analyzed tumors showed similar MUC-1 immunoexpression to ductal epithelial cells using both HMFG antibodies. Intraductal mucous secretion was also HMFG-1 and HMFG-2 positive. Conclusions Our results showed there are two kinds of myoepithelial cells in PA. The first cellular group is represented by the different kinds of neoplastic myoepithelial cells and is HMFG-positive. The second one is HMFG-negative and represented by the neoplastic myoepithelial cells located around the ducts.